Development of texturized vegetable protein from mung bean protein isolate and evaluation of its technofunctionality, structural, rheological and quality - Brishti, Fatema Hossain (2020)
In recent years, plant-based food proteins have surged in popularity as they are environmentally friendly and healthier compared to animal proteins. Mung bean protein also is an economic source of plant proteins with low greenhouse gas emission, thus revealing strong potential as a sustainable source to replace animal protein. In general, mung bean remains underutilized due to its hard-to-cook characteristics. Therefore, the objectives of this research were to prepare and characterize protein isolate from mung bean for the production of texturized mung bean protein using extrusion technology to raise its status from an underutilized food protein source while mitigating its hard-tocook phenomenon in an attempt to attain global food security goals. Mung bean protein isolate (MBPI) was produced in a lab-scale using alkaline extraction with subsequent isoelectric precipitation and compared with soy protein isolate (SPI) in terms of proximate composition, amino acid profile, techno-functional and thermal properties. The protein content, solubility profile, water and oil absorption capacities, and emulsion activity were found to be comparable with SPI. MBPI showed slightly better gelling capacity by exhibiting least gelation concentration at 12% than SPI 14%. Relatively, the denaturation temperature of MBPI (157.9ºC) was high while low denaturation enthalpy (41.6, J g-1) was observed compared to SPI indicating the comparatively less compact structure of MBPI which may aid in protein unfolding and fibril structure formation during texturization. Following this, MBPI was produced in a pilot-scale using 100 L bioreactor and three different drying techniques evaluated i.e. freeze, spray, and oven drying techniques prior to analyzing the physicochemical, techno-functional, thermal, structural, and rheological properties of protein. Freeze-dried MBPI (FD) showed the highest protein solubility and oil absorption capacity when compared to spray-dried (SD) and oven-dried (OD) MBPI. All samples showed no dissociation of protein subunits in SDS-PAGE and were thermally stable with high denaturation temperature ranging from 157.9–158.1ºC. FD MBPI and SD MBPI formed elastic gels with better gelling capacity than OD MBPI which formed aggregated gel. Current work validated the different final properties achieved for MBPI produced under different drying techniques that would allow tailoring for different food systems, whereby FD MBPI would be ideal for meat extender. Thus, FD MBPI having the best techno-functional properties was then used to produce texturized mung bean protein (TMBP) using HTST (High-temperature, short-time) extrusion processing. TMBP with desirable physical properties was produced through optimization of extrusion processing parameters of feed moisture (30–60%), screw speed (70–100 rpm), and barrel temperature (120–170 ºC) using response surface methodology. The optimum processing parameters were 49% feed moisture, 81 rpm screw speed, and 145 ºC barrel temperature. Under these conditions, microstructure analysis revealed fibrous structure in TMBP while SDS-PAGE showed partial protein unfolding that was crucial for protein fibril formation during texturization. Feed moisture, at both low (19-30%) and high ends (60– 70%), caused complete protein denaturation, irrespective of barrel temperature and screw speed, as illustrated by the disappearance of the majority of the protein gel bands on SDS-PAGE. Therefore, MBPI was then texturized at different feed moisture contents (30, 49, and 60%) and at constant barrel temperature (145 ºC) to evaluate the changes in protein profile, solubility, thermal, structural and rheological properties. Extrusion at intermediate (49%) feed moisture produced TMBP with favourable partial denaturation, the formation of small aggregates, improved solubility, and digestibility with strong gelforming behaviour. In contrast, low (30%) and high (60%) moisture content resulted in complete protein denaturation, the undesirable formation of large aggregates and weak gels. This work established that protein denaturation and formation of aggregates could be controlled by critically controlling feed moisture content and 49% feed moisture produced TMBP with desirable qualities, fostering its use as plant-based meat extender. Finally, the techno-functionality, anti-nutrient, in vivo protein quality, and toxicity of texturized mung bean protein (TMBP) were evaluated. The findings showed that extrusion successfully produced TMBP with improved techno-functionalities that are crucial for meat-based food product application, credited to retained juiciness and fatbinding ability. Alkaline protein extraction and extrusion significantly reduced trypsin inhibitor, phytic acid, and tannin content in TMBP. In vivo study revealed true protein digestibility of TMBP was 99.3% resembling casein (99.4%, control protein). Lean muscle weight gain and reduced cholesterol and triglyceride had reflected TMBP’s potential as protein meal replacer and supplement diet. Serum biochemical analysis showed no remarkable deviation from casein while microanatomy study revealed healthy heart, liver, kidney, lung, and testes in TMBP-fed group. This study ascertained the safety of alkaline extraction and extrusion to produce TMBP with improved technofunctionalities, and reduced anti-nutritional factors. Conclusively, current study successfully demonstrated the optimized production of TMBP from mung bean protein and its potential use as plant-based meat extender to serve as a healthier, safe, and sustainable protein source.